GRAPPLE SAW’S OPERATING CONDITIONS INFLUENCE ON THE PRODUCTIVITY AND COST OF PROCESSING FELLED TREES - Simões, Danilo [UNESP]; Avelino, Lara Tatiane [UNESP]; Munis, Rafaele Almeida [UNESP]; Batistela, Gislaine Cristina [UNESP]; Miyajima, Ricardo Hideaki [UNESP] (Universidade Federal do Paraná, 2022)
In the full-tree system, one of the self-propelled forest machines used is the grapple saw, which uses mechanical force to delimbing and crosscutting stems, commonly in processing yards or on the sides of forest roads. Thus, several factors can influence the machine's effective productivity, and consequently, the production costs. Hence, the objective was to analyze the influence of the slope of the land on the productivity and production costs of the grapple saw under different operational conditions. The study was carried out in a forested area, in which there were clonal forests of Eucalyptus urograndis. The processing felled trees operation was performed with a grapple saw capable of accumulating and cutting the 0.85 m² tree bundles in two operating conditions. For the production forecast, the time study was applied, associating it to the volume of drawn wood and the effective work time, accordingly, it was possible to estimate the production cost of the grapple saw. The results allowed to conclude that the effective hourly productivity and the production cost of the log tracing are associated with the slope of the land.
Influência das condições operacionais da grapple saw na produtividade e custos do processamento de árvores derrubadas
Keywords: Economic analysis; Forest planning; Land slope; Timber harvesting; Time studies